A prospective study on the variation in falling and fall risk among community-dwelling older citizens in 12 European countries. Issue 6 (30th June 2017) - Franse, Carmen B; Rietjens, Judith AC; Burdorf, Alex; van Grieken, Amy; Korfage, Ida J; van der Heide, Agnes; Mattace Raso, Francesco; van Beeck, Ed; Raat, Hein
Abstract : Objectives: The rate of falling among older citizens appears to vary across different countries, but the underlying aspects causing this variation are unexplained. We aim to describe between-country variation in falling and explore whether intrinsic fall risk factors can explain possible variation. Design: Prospective study on data from the cross-national Survey of Health, Ageing and Retirement in Europe (SHARE). Setting: Twelve European countries (Austria, Belgium, Czech Republic, Denmark, Estonia, France, Germany, Italy, The Netherlands, Spain, Sweden, Switzerland). Participants: Community-dwelling persons aged ≥65 years (n=18 596). Measurements: Socio-demographic factors (age, gender, education level and living situation) and intrinsic fall risk factors (less than good self-rated health (SRH), mobility limitations, limitations with activities of daily living (ADL), dizziness, impaired vision, depression and impaired cognition) were assessed in a baseline interview. Falling was assessed 2 years later by asking whether the participant had fallen within the 6 months prior to the follow-up interview. Results: There was significant between-country variation in the rate of falling (varying from 7.9% in Switzerland to 16.2% in the Czech Republic). The prevalence of intrinsic fall risk factors varied twofold to fourfold between countries. Associations between factors age ≥80 years, less than good SRH, mobility limitations, ADL limitations, dizziness and depression, and falling were different between countries (p<0.05). Between-country differences in falling largely persisted after adjusting for socio-demographic differences but strongly attenuated after adjusting for differences in intrinsic fall risk factors. Conclusion: There is considerable variation in the rate of falling between European countries, which can largely be explained by between-country variation in the prevalence of intrinsic fall risk factors. There are also country-specific variations in the association between these intrinsic risk factors and falling. These findings emphasise the importance of addressing intrinsic fall risk in (inter)national fall-prevention strategies, while highlighting country-specific priorities.